(untitled) (The Research of Medical Science Review, 2024)
Gestational diabetes mellitus (GDM) is a global condition where pregnant women experience high blood sugar levels. It poses risks to both maternal and fetal health. Identifying modifiable risk factors, such as pre pregnancy obesity, is crucial in managing GDM and its complications. It is important to determine the modifiable risk factors associated with GDM. Pre Pregnancy Obesity, a well-established risk factor for various pregnancy complications, has been suggested to be closely linked with the development of GDM. Objective of this study was to determine the association of GDM with pre pregnancy obesity of women. This cross-sectional study was conducted at Fauji Foundation Hospital Rawalpindi from March, 2023 to June, 2023. 100 pregnant women, aged 19-39 years with gestational age more than 20 weeks were included. Fifty women with GDM were taken in group A while 50 non-GDM women in group B. OGTT (oral glucose tolerance test) were used to diagnose the GDM. Data was collected by using a self-designed questionnaire including anthropometric measurements. Data was analyzed through an appropriate study design. In GDM group BMI ranges from 21.1 to 41.3. Obese were 38%, overweight found 46% while within normal BMI were about 16%. While in Non GDM group the BMI values range from 18.1 to 30.6, in which majority 56%falls in normal BMI, 26% falls in overweight, 14% were in obese category while 4% were found in underweight prepregnancy BMI. Study findings also revealed a statistically significant association (P≤0.05) between pre pregnancy obesity and GDM. Women with higher pre-pregnancy BMI were at a heightened risk of developing GDM.